Person Deixis in Joko Widodo’s Speech : A Pragmatic Analysis - Maimunah Ritonga (English Lecturers and Teachers Association (ELTA), 2023)
One of the speeches that was quite interesting during the COVID-19 pandemic was President Joko Widodo's speech at the plenary meeting at the Istana Negara Republik Indonesia in 2020. In that speech, President Joko Widodo scolded the ministers for their ineffective performance. Therefore, this study investigates the use of deixis in President Joko Widodo's speech at the Istana Republic Indonesia. This study was conducted by applying a qualitative descriptive method. The data from this study are videos taken from the Kompas TV YouTube channel. In the process of data analysis, the researcher conducted transcription in order to strengthen the accuracy of the data analysis and its suitability with the video. The results of data analysis indicate that in the speech of President Joko Widodo, there were 101 utterances that contained deixis. In addition, there are 5 types of deixis found in this study, namely; person, place, time, discourse, and social deixis. Keywords: Pragmatics, Deixis